GRI 306 (2016): Praktik Pengungkapan Pengelolaan Limbah Pada Industri Tambang Sektor Logam dan Mineral - Arthik Davianti; Octasari Anggi Putri (Owner : Riset dan Jurnal Akuntansi, 2022)
This research aim of learning about the disclosures made in the sustainability report based on GRI standards on the company’s CSR activities that focus on waste management. Case  occur as a result of inappropriate waste management, especially in the mining industry  which has a negative impact on society and the environment. This makes waste management practices as the company's focus related to CSR activities disclosed through sustainability reports according to GRI standards interesting to study. This research applies a qualitative approach using content analysis techniques that focus on the subject and context classified through keywords known as disclosure groups. This study focuses on the metal and mineral sector mining industry listed on the Indonesian stock exchange, especially companies that publish sustainability reports according to GRI standards for the 2018-2020 period. The results of this research are in line with the stakeholder’s theory with show indicate that based on the disclosure group, most of the observed companies have implemented waste management and have made CSR disclosures according to the GRI 306:2016 standards,as a form of corporate responsibility. In conclusion, companies that published sustainability reports based on the GRI standards presented the reports  that were complete, informative, and comprable. Accordingly, companies can increase the disclosure of CSR activities especially in term of waste management, to meet the needs of stakeholders.